Some Prototype Results of the Symmetric Regularized Long Wave Equation Arising in Nonlinear Ion Acoustic Waves - Isik, Erdem; Bulut, Hasan; Atas, Sibel Sehriban (E D P Sciences, 2017)
In this manuscript, we consider the Bernoulli sub-equation function method for obtaining new exponential prototype structures to th Symmetric Regularized Long Wave mathematical model. We obtain new results by using this technique. We plot two-and three-dimensional surfaces of the results by using Wolfram Mathematica 9. At the end of this manuscript, we submit a conclusion in the comprehensive manner.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY